The Value of Dysregulated LncRNAs on Clinicopathology and Survival in Non-Small-Cell Lung Cancer: A Systematic Review and Meta-Analysis - Wang, Juan; Han, Xu; Yuan, Ye; Gu, Hao; Liao, Xing; Jiang, Miao (Frontiers in Genetics, 2022)
Background Accumulating evidence has suggested a number of lncRNAs are involved in non-small-cell lung cancer (NSCLC) pathogenesis. However, results about lncRNA expressions in NSCLC patients are still inconclusive. Therefore, we performed a systematic review of the studies to collect and examine all evidence on the potential role of lncRNAs in order to better understand the involvement of lncRNAs in the development of NSCLC. Methods We systematically searched through seven literature databases to identify all published studies that evaluated the expression of one or more lncRNA between human samples with NSCLC (cases) and without NSCLC (controls) from 1 January 1995 to 24 May 2021. Quality assessment of studies was conducted according to the ‘Quality in Prognosis Studies’ (QUIPS) tool, and the heterogeneity across studies was using the I-squared statistic and chi-square-based Q-tests. Either fixed or random-effects meta-analysis was performed to summarize effect size to investigate the association between the lncRNA expression and overall survival (OS), disease-free survival (DFS), progress-free survival (PFS), and clinicopathological features. R statistical software program is used to conduct standard meta-analysis. Results We finally obtained 48 studies with 5211 patients included in this review after the application of the eligible criteria. Among the 48 lncRNAs, 38 lncRNAs were consistently upregulated and 10 were deregulated in patients with NSCLC compared to controls. The upregulated lncRNAs were positively associated with histological type, TNM stages, lymph node metastasis, differentiation grade, distant metastasis, tumor size and overall survival ( p<0.05). Especially, five upregulated lncRNAs (linc01234, ZEB1-AS1, linc00152, PVT1 and BANCR) were strongly associated with TNM Ⅲa stage (n=5, OR=4.07, 95%CI: 2.63-6.28, P<0.01). However, 10 deregulated lncRNAs were not significantly associated to the clinicopathological features and overall survival in NSCLC in the meta-analysis (P≥0.05). Conclusion This systematic review suggests high expression of upregulated lncRNAs could be served as promising biomarkers for prognosis of NSCLC. The prognostic value of downregulated lncRNA in NSCLC needed to be further explored.